2004
DOI: 10.1590/s0100-204x2004000800009
|View full text |Cite
|
Sign up to set email alerts
|

Sorção do herbicida imazaquin em Latossolo sob plantio direto e convencional

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da variabilidade do pH e da matéria orgânica de um Latossolo Vermelho distrófico, textura argilosa, sob diferentes manejos na retenção do herbicida imazaquin. A retenção deste herbicida foi medida pelo coeficiente de partição solo-água (K d ) em amostras de solos coletados na camada superficial (0-15 cm) em área de 38 ha, sob irrigação com pivô central e plantio direto e convencional. A retenção do imazaquin foi maior nas áreas com menores valores de pH e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
6
0
6
Order By: Relevance
“…It is known that its adsorption determines how much of the herbicide will be sorbed to the soil matrix and how much is available in the solution. For weak acid herbicides low soil pH provides higher adsorption (Bresnaham et al, 2000;Madani et al 2003;Oliveira et al, 2004), which are less available to plants. The rice soils of Rio Grande do Sul state are predominantly acidic in its natural condition, and approximately 50% of them have pH lower than 5 (Anghinoni et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that its adsorption determines how much of the herbicide will be sorbed to the soil matrix and how much is available in the solution. For weak acid herbicides low soil pH provides higher adsorption (Bresnaham et al, 2000;Madani et al 2003;Oliveira et al, 2004), which are less available to plants. The rice soils of Rio Grande do Sul state are predominantly acidic in its natural condition, and approximately 50% of them have pH lower than 5 (Anghinoni et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Trabalho realizado por Oliveira et al (2004) evidenciou influência do pH na retenção de herbicidas. A retenção do imazaquin foi maior nas áreas com menores valores de pH e altos teores de matéria orgânica.…”
Section: Introductionunclassified
“…Given the above, Ying & Williams (2000) reported that oxadiazon is highly sorbed in the soil, with high K d , varying from 23.43 to 28.07 mL g -1 , and K oc, of 2.343 to 2.718 mL g -1 , in soils with pH 7.2, 45.5% of clay and 1.00% of OC and with pH 4.7, 3.0% of clay and 0.86% of OC, respectively; from these results, the authors claim that the sorption of oxadiazon is clearly not related to the clay content of the soil, but with the OC content. The highest values of this coefficient are indicative of better retention of the herbicide by the soil and, consequently, less leaching (Oliveira et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The imazaquin sorption is higher in samples with lower pH values and higher levels of OM; therefore, the effect of the OM on retention of imazaquin is pH dependent (Oliveira et al, 2004). Conditions of soils with low pH values tend to increase the interaction between molecules of the herbicide and the colloids in the soil, especially by the OC (Berglof et al, 2003).…”
Section: Resultsmentioning
confidence: 99%